Peran Kepemimpinan, Kompetensi Pengelola dan Partisipasi Anggota Terhadap Kinerja Koperasi - Rohmat Nurhidayat (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to determine the effect of leadership, managerial competence, and member participationon the performance of cooperatives at the Al Ihya Pamarican Islamic Boarding School, Ciamis Regency, West Java Province.The method used is a quantitative approach,population of data collected in the study is allcooperative members totaling 34 people and all of them are used as objects of research. While sampling using non-probability sampling technique that does not provide equal opportunities for elements of the population to be selected as samples. Furthermore, the test used to test the research instrument is in the form of validity and reliability tests. Hypothesis testing using T test and F test, while data analysis using multiple linear regression analysis.The results of the study stated that leadership, management competence, and member participation had an effect simultaneously or partially on the performance of cooperatives